Energy and life cycle impact assessment for xylitol production from corncob - Dasgupta, Diptarka; Sidana, Arushdeep; Ghosh, Prasenjit; Sharma, Tripti; Singh, Jasvinder; Prabhune, Asmita; More, Snehal; Bhaskar, Thallada; Ghosh, Debashish (Journal of Cleaner Production, 2021)
The conversion of biobased feedstocks into energy and value-added chemicals is one main approach to address the current global challenge for waste mitigation through the biorefinery mode. Corncob biomass which is one of the most abundant agricultural residue in India with a high hemicellulose content, can serve as a potential low-cost raw material for food-grade xylitol production. The present study demonstrates a process for xylitol production from corncob biomass with detailed energy and life cycle analysis for viability assessment. The major highlight of the process is the use of microbial fermentation, where biomass-derived D-xylose is converted to xylitol with high selectivity. Overall, 0.502 kg of xylitol crystals could be produced from 3.5 kg of corncob biomass. Simulation analysis revealed that the evaporators are the primary consumers of energy, and the process of heat integration can significantly reduce the energy requirements of the overall process. Environmental impacts of the system evaluated showed emission results of 8.68 kg CO2 equivalent and revealed that marine aquatic and freshwater eco-toxicity are the only possible contributors to the environment. The results suggest that the process would have favourable energy balances, which can be used in pilot plant and heat exchanger network design and operation for xylitol production scale up to 500 L. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: biomass valorization; Life cycle impact assessment; simulation; xylitol

Process development for crystalline xylitol production from corncob biomass by Pichia caribbica - Dasgupta, Diptarka; Sidana, Arushdeep; Sarkar, Bipul; More, Snehal; Ghosh, Debashish; Bhaskar, Thallada; Ray, Anjan (Food and Bioproducts Processing, 2022)
Xylitol, a commodity chemical, is widely used in nutraceutical and pharmaceutical formulations. Microbial xylitol production is a promising alternative to mitigate current industrial practice issues and offers an environment-friendly sustainable conversion route. This study demonstrates a bioprocess for xylitol production from corncob using a mesophilic yeast Pichia caribbica. Corncob was hydrolyzed by dilute acid and steam explosion to recover fermentable xylose and used as the feed for xylitol production. Activated carbon treatment (3% w/v) completely removed the biomass-derived inhibitors furfural and hydroxymethyl furfural from the liquid hydrolysate. The fermenting yeast Pichia caribbica produced 124.1 +/- 0.45 g/L xylitol from the detoxified and concentrated corncob hydrolysate with a high yield of 0.80 +/- 0.02 g/g. The crystallized xylitol with 96.5% purity demonstrated no harmful effects on the cell line used as a control for the in-vitro toxicity studies. This proof of concept can be applied to help scale up for bio-refinery-based large-scale production of xylitol from corncob biomass.(c) 2022 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Biomass; Corncob; Detoxification; Fermentation; Toxicity analysis; xylitol